Low-Temperature Synthesis of GeTe Nanoparticles - Bouška, Marek; Milasheuskaya, Yaraslava; Slouf, Miroslav; Knotek, Petr; Pechev, Stanislav; Prokes, Lubomir; Pecinka, Lukas; Havel, Josef; Novák, Miroslav; Jambor, Roman; Němec, Petr (Wiley-VCH, 2024)
Nanoparticles can offer an alternative approach to fabricate phase-change materials. The chemical synthesis of GeTe nanoparticles using organometallic precursors exploits high-boiling solvents and relatively high temperatures (close or even above crystallization temperatures), as reported in the available literature. The aim of this work is the preparation of GeTe nanoparticles by a low-temperature synthetic method exploiting new organometallic precursors and common organic solvents. Indeed, different preparation methods and characterization of GeTe nanoparticles is discussed. The characterization of the prepared nanomaterial was performed on the basis of X-ray diffraction, transmission electron microscopy, scanning electron microscopy with energy dispersive X-ray spectroscopy, laser ablation time-of-flight mass spectrometry, Raman scattering spectroscopy, and dynamic light scattering. The results show that the low-temperature synthetic route leads to amorphous GeTe nanoparticles. Exploited organometallic precursor is stabilised by neutral ligand which can be isolated after the reaction and repeatedly used for further reactions. Furthermore, GeTe nanoparticle size can be tuned by the conditions of the synthesis. The aim of this work is preparation of GeTe nanoparticles by low temperature synthetic method exploiting new organometallic precursors. The GeTe nanoparticles are amorphous and characterized by X-ray diffraction, transmission and scanning electron microscopy with energy dispersive X-ray spectroscopy, laser ablation time-of-flight mass spectrometry, Raman scattering spectroscopy and dynamic light scattering. image
Nízkoteplotní syntéza nanočástic GeTe
Keywords: Nanoparticles; Chalcogenides; GeTe; Organometallic precursor; nanočástice; chalkogenidy; GeTe